Effect of Bank Merger on the Shareholders Wealth and Post-Merger Situation of Nepalese Banking Industry - Bhatta, Manoj Kumar (Information Management and Business Review, 2016)
This research studies the effect of independent variables such as cost efficiency, ROA, ROE and Capital on dependent variable EPS of the merged bank in Nepal. Various statistical tools such as mean standard deviation, correlation, regression were employed to measure the effect of bank merger on the shareholders wealth. Based on the result of study, except ROA, no other independent variable under study showed any impact on earnings per share. The superior bank shareholders are not getting what they deserve and inferior bank shareholders get more than they deserve after the post-merger. It is also finding out that external factors such as earthquake, border blockade and political instability highly affects the shareholders earnings.